Analisis Tumbuh Kembang Anak Ditinjau Dari Aspek Perkembangan Motorik Halus Anak Usia Dini Kelompok B TK Aisyiyah Bustanul Athfal - Damanik, Hardianti; Nasution, Liza Khanafathy; Daulay, Mutiara Mastina Fitri; Pratiwi, Yulia Winda; Margolang, Zenny Fitria Syahri (Universitas Muhammadiyah Sumatera Utara, 2022)
The golden age in humans occurs from the time the child is born to the age of eight. At this time the growth and development of children is going fast, so it needs effective stimulation from parents and their environment. Growth is a change that is in each individual. While development is a qualitative process that refers to the perfection of social and psychological functions in a person and lasts throughout human life. In the aspect of fine motor development in early childhood, there will be continuous growth and development of children. Of course, simultaneously, the growth and development of various aspects in early childhood will run according to the stages of their age, so parents need to have thorough knowledge about various aspects of early childhood.